2012
DOI: 10.2298/jsc120106084d
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of SPE-HPLC method for the determination of carbamazepine and its metabolites carbamazepine epoxide and carbamazepine trans-diol in plasma

Abstract: SPE-HPLC method has been developed and validated for rapid analysis of carbamazepine and its two metabolites carbamazepine epoxide and carbamazepine trans-diol in human plasma. The analysis was performed using C18 Bakerbond-BDC analytical column (250 mm x 4.6 mm i.d., particle size 5 μm). The optimal conditions for the separation were established with the mobile phase acetonitrile - 10 mM phosphate buffer, pH 7.0 (30:70, v/v) at the flow rate of 1.5 mL min-1, temperature 35°C, and UV detection at 210 nm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The amount of CBZ was estimated as per the method reported by Džodić et al [ 36 ] using reverse-phase HPLC. The HPLC system (Shimadzu, Kyoto, Japan) comprised dual piston pumps, an auto sampler, a UV-visible detector, and LC solution software.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of CBZ was estimated as per the method reported by Džodić et al [ 36 ] using reverse-phase HPLC. The HPLC system (Shimadzu, Kyoto, Japan) comprised dual piston pumps, an auto sampler, a UV-visible detector, and LC solution software.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison of extraction time of the proposed method with solid-phase microextraction (SPME), 32 liquid-liquid extraction (LLE), 33,34 and solid-phase extraction (SPE) 35 for the extraction of the target analytes indicates that this novel method has a very short equilibrium time comparing to the mentioned methods and the extraction time needed for the proposed method is a few seconds. Quantitative results of the proposed method are better than for SPE 35 and LLE 33,34 methods. Relative standard deviation (RSD%) of the proposed method is better than for SPME 32 and LLE 33 methods.…”
Section: Analytical Performance and Methods Validationmentioning
confidence: 99%
“…One of the simplest and most accurate methods is highperformance liquid chromatography (HPLC) [1]. Previous studies indicated that HPLC was adequate, effective, suitable, simple, rapid, highly sensitive, also had a good intra-day and inter-day precision and an accuracy of >90% [1][2][3][4][5][6]. Considering many patients also use other AEDs, the physician has to make sure that the measurement of carbamazepine plasma levels is unaffected by the presence of other AED.…”
Section: Introductionmentioning
confidence: 99%